Intimacy, Trust, and Justice on The Greatest Menace, a Podcast Exposing a “Gay Prison” - Siobhán McHugh (Media and Communication)
In the tradition of narrative podcasts exposing historical injustices, The Greatest Menace (TGM) examines how a government-run prison in Australia used those imprisoned to study the causes and treatments of homosexuality. Hosted by gay Arab-Australian journalist Patrick Abboud, TGM interweaves Abboud’s struggle for acceptance in his homophobic community with his forensic documentation of lives ruined by a society where homosexuality was illegal till 1984. Gay men entrust Abboud with their experiences of aversion therapy and estrangement from family; a former cop reveals how he entrapped, then arrested, gay men; a trans woman runs away to New Zealand after being imprisoned. TGM charts the palpable intimacy between Abboud and most of his informants, but as this article explores, the podcast also held potential for the privileging of activism over ethics. The cop could have been depicted as evil, but in pursuit of fairness, the TGM team settled on a more nuanced portrayal. An evangelical interviewee conflates “homosexual” with “paedophile” to Abboud’s face; he retaliates by recording his meta-fury and writing it into the script. Intimacy and trust are intertwined as Abboud and his mother navigate the shame and fear that shadowed his coming out. Using textual analysis, semi-structured interviews, iterative scripts, reflexive practice, and theory of audio storytelling and podcast intimacy, this article analyses, from an autoethnographic insider/maker perspective, how the producers of this acclaimed podcast (17 awards) balanced intimacy and trust while exposing historic queer true crime in all its messy humanity.